Temperature drift modeling and compensation of micro-electro-mechanical system gyroscope based on improved support vector machine algorithms. (March 2020) - Wang, Xinwang; Cao, Huiliang
This article suggested two methods to compensate for the temperature drift of the micro-electro-mechanical system gyroscopes, which are support vector machine method and C-means support vector machine. The output of X axis which was ranged from −40°C to 60°C based on the micro-electro-mechanical system gyroscope is reduced and analyzed in this article. The results showed the correctness of the two methods. The final results indicate that when the temperature is ranged from −40°C to 60°C, the factor of B is reduced from 0.424 ( ° h ) to 0.02194 ( ° h ), and when the temperature is ranged from 60°C to −40°C, the factor of B is reduced from 0.1056( ° h ) to 0.0329( ° h ), and the temperature drift trend and noise characteristics are improved clearly.